반응형
derivative_br_11

11. ddxex+ex\frac{d}{dx} \sqrt{e^x}+e^{\sqrt{x}}

ddxex+ex=(ex2)+(ex12)=ex2(12)+ex(12x)=12ex+ex2x \begin{aligned} &\frac{d}{dx} \sqrt{e^x}+e^{\sqrt{x}}\\ &=(e^{\frac{x}{2}})' + (e^{x^{\frac{1}{2}}})'\\ &=e^{\frac{x}{2}}(\frac{1}{2})+e^{\sqrt{x}}(\frac{1}{2\sqrt{x}})\\ &=\frac{1}{2}\sqrt{e^x}+\frac{e^{\sqrt{x}}}{2\sqrt{x}} \end{aligned}


12. ddxsec3(2x)\frac{d}{dx} sec^3(2x)

ddxsec3(2x)=3sec2(2x)(sec(2x)tan(2x))2=6sec3(2x)tan(2x) \begin{aligned} &\frac{d}{dx} sec^3(2x)\\ &=3sec^2(2x)(sec(2x)tan(2x))2\\ &=6sec^3(2x)tan(2x) \end{aligned}


13. ddx12(secx)(tanx)+12ln(secx+tanx)\frac{d}{dx} \frac{1}{2} (secx)(tanx) + \frac{1}{2} ln(secx + tanx)

ddx12(secx)(tanx)+12ln(secx+tanx)=12(secxtanxtanx+secxsec2x)+12(secx+tanx)(secxtanx+sec2x)=12secx(tan2x+sec2x)+secx(tanx+secx)2(secx+tanx)=12secx(1+tan2x+sec2x)=12secx2sec2x=sec3x \begin{aligned} &\frac{d}{dx} \frac{1}{2} (secx)(tanx) + \frac{1}{2} ln(secx + tanx)\\ &=\frac{1}{2}(secxtanxtanx+secxsec^2x)+\frac{1}{2(secx+tanx)}(secxtanx+sec^2x)\\ &=\frac{1}{2}sec x(tan^2x+sec^2x)+\frac{secx(tanx+secx)}{2(secx+tanx)}\\ &=\frac{1}{2}secx(1+tan^2x+sec^2x)=\frac{1}{2}secx 2sec^2x\\ &=sec^3x \end{aligned}


14. ddx(xex)/(1+ex)\frac{d}{dx} (xe^x)/(1+e^x)

ddxxex1+ex((xex)=ex+xex)=(xex)(1+ex)(xex)(1+ex)(1+ex)2=(ex+xex)(1+ex)(xex)(ex)(1+ex)2=ex(1+x)(1+ex)xe2x(1+ex)2=ex((1+xex+ex+x)xex)(1+ex)2=ex(1+ex+x)(1+ex)2 \begin{aligned} &\frac{d}{dx} \frac{xe^x}{1+e^x}\\ &((xe^x)' = e^x+xe^x)\\ &=\frac{(xe^x)'(1+e^x) - (xe^x)(1+e^x)'}{(1+e^x)^2}\\ &=\frac{(e^x+xe^x)(1+e^x) - (xe^x)(e^x)}{(1+e^x)^2}\\ &=\frac{e^x(1+x)(1+e^x)-xe^{2x}}{(1+e^x)^2}\\ &=\frac{e^x((1+xe^x+e^x+x)-xe^{x})}{(1+e^x)^2}\\ &=\frac{e^x(1+e^x+x)}{(1+e^x)^2}\\ \end{aligned}


15. ddx(e4x)(cos(x/2))\frac{d}{dx} (e^{4x})(cos(x/2))

ddx(e4x)(cos(x2))=(e4x)(cos(x2))+(e4x)(cos(x2))=(e4x4)cos(x2)+e4x(sin(x2)12)=4e4xcos(x2)12e4xsin(x2) \begin{aligned} &\frac{d}{dx} (e^{4x})(cos(\frac{x}{2}))\\ &=(e^{4x})'(cos(\frac{x}{2}))+(e^{4x})(cos(\frac{x}{2}))'\\ &=(e^{4x}4)cos(\frac{x}{2})+e^{4x}(-sin(\frac{x}{2})\frac{1}{2})\\ &=4e^{4x}cos(\frac{x}{2})-\frac{1}{2}e^{4x}sin(\frac{x}{2}) \end{aligned}


16. ddx1x324\frac{d}{dx} \frac{1}{\sqrt[4]{x^3 - 2}}

ddx1x324=ddx(x32)14=14(x32)54(3x2)=3x24(x32)x324=3x24(x32)54 \begin{aligned} &\frac{d}{dx} \frac{1}{\sqrt[4]{x^3 - 2}}=\frac{d}{dx} (x^3 - 2)^{-\frac{1}{4}}\\ &=-\frac{1}{4} (x^3 - 2)^{-\frac{5}{4}}(3x^2)\\ &=-\frac{3x^2}{4(x^3-2)\sqrt[4]{x^3 - 2}}\\ &=-\frac{3x^2}{4\sqrt[4]{(x^3 - 2)^5}}\\ \end{aligned}


17. ddxarctan(sqrt(x21))\frac{d}{dx} arctan(sqrt(x^2-1))

ddxtan1(x21)(y=arctan(x),tany=x,sec2ydy=dx)(R.Tangle=y,a=1,o=x,h=1+x2)(dy/dx=1sec2y=cos2y=11+x2)=cos2(tan1(x21))12x212x=cos2(tan1(x21))xx21=11+x21xx21=1xx21 \begin{aligned} &\frac{d}{dx} tan^{-1}(\sqrt{x^2-1})\\ & (y=arctan (x), tan y=x, sec^2ydy=dx)\\ &(R.T angle=y, a=1, o=x, h=\sqrt{1+x^2})\\ & (dy/dx = \frac{1}{sec^2y}=cos^2y=\frac{1}{1+x^2})\\ &=cos^2(tan^{-1}(\sqrt{x^2-1}))\frac{1}{2\sqrt{x^2-1}}2x\\ &=cos^2(tan^{-1}(\sqrt{x^2-1}))\frac{x}{\sqrt{x^2-1}}\\ &=\frac{1}{1+x^2-1}\frac{x}{\sqrt{x^2-1}}\\ &=\frac{1}{x\sqrt{x^2-1}} \end{aligned}


18. ddx(lnx)/x3\frac{d}{dx} (lnx)/x^3

ddxlnxx3=1xx3lnx(3x2)x6=x23x2lnxx6=13lnxx4 \begin{aligned} &\frac{d}{dx} \frac{lnx}{x^3}=\frac{\frac{1}{x}x^3-lnx(3x^2)}{x^6}\\ &=\frac{x^2-3x^2lnx}{x^6}=\frac{1-3lnx}{x^4} \end{aligned}


19. ddxxx\frac{d}{dx} x^x

ddxxx(y=xx,logxy=x,lnylnx=x)(lny=xlnx,1ydy=(lnx+1)dx)dydx=(1+lnx)y=(1+lnx)xx \begin{aligned} &\frac{d}{dx} x^x\\ &(y=x^x, log_xy=x, \frac{ln y}{ln x}=x)\\ &(lny = xlnx, \frac{1}{y}dy=(lnx+1)dx)\\ &\frac{dy}{dx}=(1+lnx)y=(1+lnx)x^x \end{aligned}
Alt.
ddxxx,(x=elnx)=ddx(elnx)x=ddx(exlnx)=exlnx(lnx+1)=xx(lnx+1) \frac{d}{dx} x^x, (x=e^{lnx})\\ =\frac{d}{dx} (e^{lnx})^x=\frac{d}{dx} (e^{xlnx})\\ =e^{xlnx}(lnx+1)\\ =x^x(lnx+1)


20. ddx(x3+y3=6xy)\frac{d}{dx}(x^3+y^3=6xy)

ddx(x3+y3=6xy)3x2dx+3y2dy=6ydx+6xdy(3x26y)dx=(6x3y2)dydydx=3x26y6x3y2=x22y2xy2 \begin{aligned} &\frac{d}{dx}(x^3+y^3=6xy) \\ &3x^2dx+3y^2dy=6ydx+6xdy\\ &(3x^2-6y)dx=(6x-3y^2)dy\\ &\frac{dy}{dx}=\frac{3x^2-6y}{6x-3y^2}\\ &=\frac{x^2-2y}{2x-y^2} \end{aligned}
Alt.
x3+y3=6xy:(Dx)3x2+3y2y=6y+6xy(3x26y)=(6x3y2)yy=3x26y6x3y2=x22y2xy2 \begin{aligned} &x^3+y^3=6xy :(Dx)\\ &3x^2+3y^2y'=6y+6xy'\\ &(3x^2-6y)=(6x-3y^2)y'\\ &y'=\frac{3x^2-6y}{6x-3y^2}\\ &=\frac{x^2-2y}{2x-y^2} \end{aligned}


Author: crazyj7@gmail.com

'Math' 카테고리의 다른 글

derivative100 [31-40]  (0) 2019.11.05
derivative100 [21-30]  (0) 2019.11.04
derivative100 [1-10]  (0) 2019.10.30
Integral100 [91-100]  (1) 2019.10.27
Integral100 [90]  (2) 2019.10.27

+ Recent posts